2020
DOI: 10.2147/ppa.s244273
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metformin Improves the Depression Symptoms of Women with Polycystic Ovary Syndrome in a Lifestyle Modification Program</p>

Abstract: Background: Metformin is commonly prescribed to manage polycystic ovary syndrome (PCOS), which is one of the most common endocrine disorders among women of childbearing age and is associated with high prevalence rates of depression and anxiety.Objective: This study's objective was to determine the impact of prescribed metformin on depression and anxiety levels of patients with PCOS. Methods: This prospective, multi-center, cohort study examined the impact of prescribed metformin on the depression and anxiety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 68 publications
0
31
1
Order By: Relevance
“…Fasting mimetics, such as rapamycin and metformin, are used to influence signaling involved in dietary restriction without actual calorie restriction [ 87 ]. Metformin is reported to mitigate symptoms of depression and treat common endocrine disorders among women of childbearing age (e.g., polycystic ovary syndrome) [ 89 ].…”
Section: Dietary Interventions For Gestational Diabetesmentioning
confidence: 99%
“…Fasting mimetics, such as rapamycin and metformin, are used to influence signaling involved in dietary restriction without actual calorie restriction [ 87 ]. Metformin is reported to mitigate symptoms of depression and treat common endocrine disorders among women of childbearing age (e.g., polycystic ovary syndrome) [ 89 ].…”
Section: Dietary Interventions For Gestational Diabetesmentioning
confidence: 99%
“…23 Early screening allows for adequate treatment to begin as soon as possible and is important for the prevention of a worse mental state which will affect the patient's quality of life. 7 Lifestyle changes like a healthy diet and physical changes are advised as first-line treatment options for PCOS, both interventions have been linked to a reduction in depression and elevated quality of life. 24 Physical activity reduces insulin resistance, improves body image and the metabolic and reproductive features of PCOS, and group exercise has been linked to better mental health outcomes since it is a great way to have a form of accountability and support.…”
Section: Management For the Mental Health Symptoms For Pcosmentioning
confidence: 99%
“…4,5 PCOS can also increase women's risk of type 2 diabetes, cardiovascular disease, infertility, anxiety and depression, and poor health-related quality of life. [6][7][8] The signs and symptoms usually develop in menarche and they vary from woman to woman. 9,10 These changes may be in response to obesity causing irregular or prolonged cycles with more than 35-day intervals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective, multi-centre cohort study conducted in four gynaecology clinics showed that women with polycystic ovary syndrome (PCOS) receiving metformin combined with lifestyle modifications improved their mental well-being [ 6 ]. Moreover, among elderly subjects with diabetes, depression was not uncommon, while its presence was reduced by metformin therapy [ 7 ].…”
Section: Digital Featuresmentioning
confidence: 99%